MicroRNAs from Yishen Tongluo formula can repair sperm DNA damage caused by benzo(a)pyrene - Chenming Zhang; Ruimin Ma; Wenbang Liu; Sicheng Ma; Zulong Wang; Zixue Sun (Taylor & Francis Group, 2024)
Context Plant microRNAs (miRNAs) present in Yishen Tongluo formula (YSTL, a traditional Chinese herbal medicine formula) are considered as potential therapeutic drugs for reducing the sperm DNA fragmentation index (DFI).Objective To study the effectiveness of plant miRNAs in YSTL for repairing mouse sperm DNA damage caused by benzo(a)pyrene (BaP).Methods and materials Twenty-four male SPF ICR (CD1) mice were divided into control, BaP and YSTL groups. A BaP-induced (100 mg/kg) sperm DNA damage model was established in the BaP and YSTL groups, and the mice in the YSTL group were treated with YSTL (23.78 g/kg) for 8 weeks. Sperm DFI was determined via a sperm chromatin structure assay (SCSA). MicroRNAs in the testes of the mice were analysed via RNA-seq, and the top four plant miRNAs were screened, identified and overexpressed in GC cells. The effects of plant miRNAs on the viability and DNA integrity of GC cells exposed to benzo(a)pyrene diol epoxide (BPDE) (1 μM) were tested using CCK8 and comet assays.Results Compared with that of the BaP group, the DFI of the YSTL group decreased (9.57% vs. 18.54%, F = 18.645, p = 0.0236). miR166-y, miR894-x, miR822-x and miR396-x were screened. The CCK8 and comet assays revealed that the DFI of the mimic group was significantly lower than that of the BPDE (IC50 = 1.006 μM) group, with the most significant difference in the miR396-x group.Discussion and Conclusions Plant miRNAs such as miR396-x can penetrate the blood-testis barrier through the digestive system to repair sperm DNA.